Socio-Demographic Factors Associated with the Knowledge, Attitude and Practice (KAP) of Dengue Patients of Dhaka City During 2021 Dengue Outbreak (Bangladesh Journal of Zoology, 2024)
Dengue has emerged as one of the most serious mosquito-borne viral infections, with an increasing global occurrence. In Bangladesh, it has become endemic with recurrent occurrences. The present study aims to evaluate the socio-demographic factors affecting the knowledge, attitude and practice (KAP) of 526 dengue patients of Dhaka city in 2021. As face-to-face interviews in the hospitals were prohibited due to COVID-19 restrictions during 2021, contact number of the dengue patients admitted to different hospitals of Dhaka city were obtained from Directorate General of Health Services (DGHS) and data were collected according to a questionnaire by interviewing the patients over telephone. Association between socio-demographic factors and knowledge-attitude scores, and between socio-demographic factors and practice scores were analyzed statistically. Among the 526 patients, majority were from Dhaka South City Corporation (DSCC) (53.8%), lived in small sized families (76.43%), had a Masters degree (22.43%) and a family income above 30000 BDT (Bangladeshi Taka) per month (66.92%). 74.33% patients had good level of knowledge and attitude, and 27.19% had good practice level. Education level, monthly income, area of residence and house type were associated with good knowledge and attitude but only house type was associated with good practice. A significant correlation was found between knowledge-attitude and preventive practice scores. The study findings indicate that though majority had good knowledge and attitude, people were still affected by dengue due to lack of enough preventive practices. The study suggests that there should be effective preventive practices with community participation to reduce dengue transmission.Bangladesh J. Zool. 52(2): 167-184 2024